Pengujian Performa Baterai Nickel-Metal Hydride (NiMH) Untuk Mobil Listrik Satu Penumpang Pada Kompetisi Balap Mobil Listrik Ene1-Gp Jepang 2017 - Dedy Ramdhani Harahap (Politeknik Manufaktur Negeri Bangka Belitung, 2017)
The use of electric vehicles (EVs) is viewed as an attractive solution to reduce CO2 emissions and fuel consumption resulted from transport sector, but the EVs implementation is limited to driving distance and and the charging process that inconvenience. The analysis of energy consumption characteristics of Nickel-Metal Hydride (NiMH) battery that commonly used as the energy source for EVs become an important foundation to study the durability and performance of the battery when applied in addition to increase the driving range from this EVs. This research aims to test the durability and the performance of the Eneloop type of Nickel-Metal Hydride (NiMH) battery that used for the racing car competed on ENE1-GP Japan at Suzuka Circuit Japan. From this experiment will be achieve the energy consumption estimation systematically, based on this data the parameters can be decided accurately for the EVs that attend the competition. The battery will be test under room temperature and the load given during the test from 0.1A to 10A. The average temperature during the performance test were observed using thermal camera. The best result from this experiment is on 5A, the battery will effectively use and can fit the requirement to complete the race in 18 minutes and 49 seconds for 3 cycles (laps). On the other hand, this data also can become the foundation to develop the electric vehicle which has similar specification.